A Wide Angularly Stabile Metasurface-based Band Pass Filter in Ka Band - Datta S.; Chatterjee S.; Sarkar C.; Bhattacharyya S. (My University, 2025)
In this report, a metasurface-based band-pass filter (BPF) operating between 30.3 GHz and 31.9 GHz with a fractional bandwidth of 5.2%, has been proposed for the Ka band application. Four concentric copper rings are arranged in a unit cell designed on top of an RT 6010 substrate with the completely etched backside. The unit cell dimension is 0.17λ × 0.17λ × 0.0036λ (at 31 GHz) with insertion loss 1 dB while the out of band response falls below 40 dB. The BPF shows angular stability up to 70°. © 2023 IEEE.